Teenage girls sitting in the sand in a letter y formation - Crouch, Steve, 1915-1983 (photographer):::Creator::::::::::::
Photographs shows a group portrait of teenage girls who are at Asilomar for the Y-Teens summer conference in June 1951. They are seated in the sand and are positioned to create the letter y. Asilomar is in Pacific Grove, California.